Investigating the Nexus Between Traffic Accidents and Tourism in Jordan: Evidence From the ARDL Approach - Maen Qaseem Ghadi (Journal of Engineering, Project, and Production Management, 2025)
Several studies have examined various variables to investigate the factors contributing to traffic accidents. This paper adapts the autoregressive distributed lag (ARDL) technique to examine the long-term and dynamic relationship between traffic accident indicators and tourism in Jordan. Three levels of accidents have been studied, including fatalities, severe injuries, and minor injuries, against the following independent variables: overnight visitors, same-day visitors, tourism income, and tourist rental cars. Monthly data has been collected, covering the period from 2012 to 2021. The ARDL estimates showed the presence of long-run cointegration between variables for all accident indicators. Furthermore, the ARDL estimates on the long and short run indicate a varying effect of the considered explanatory variables by accident type. The results indicate that increased tourism income has a positive effect on the risk of minor accidents in the short-term but a negative effect on fatalities and serious accidents in the long-term. Granger causality results show a strong unidirectional effect of overnight visitors, single-day visitors, and tourism income on traffic accident indicators. The results of this study can help policymakers understand the impact of some tourism variables on traffic accidents and vice versa.